Ultrahigh energy storage density and efficiency in A/B-site co-modified silver niobate relaxor antiferroelectric ceramics - Peng Shi; Jin Liu; Yuechan Song; Qiwen Chen; Hongmei Jing; Lina Liu; Xiaobin Zhou; Xiaoming Chen; Xiaojie Lou; Peng Liu (Journal of Materiomics)
AgNbO3-based antiferroelectric ceramics can be used to prepare dielectric ceramic materials with energy storage performance. However, their efficiency is much lower than that of relaxors, which is one of the biggest obstacles for their applications. To overcome this problem, AgNbO3 ceramics co-doped with Eu3+ and Ta5+ at the A- and B-sites were prepared in this work. The Ag0.97Eu0.01Nb0.85Ta0.15O3 sample has a Wr of 6.9 J/cm3 and an η of 74.6%. The ultrahigh energy storage density and efficiency of Ag0.97Eu0.01Nb0.85Ta0.15O3 has been ascribed to the synergistic effect of the increase in the breakdown electric field, the enhancement of antiferroelectric stability, the construction of multiphase coexistence, and the modification of the domain structure morphology. The Ag0.97Eu0.01Nb0.85Ta0.15O3 ceramic is expected to be one of the options for preparing dielectric capacitors.